2017
DOI: 10.1016/j.ultsonch.2017.03.014
|View full text |Cite
|
Sign up to set email alerts
|

Sonochemical rate enhanced by a new nanomagnetic embedded core/shell nanoparticles and catalytic performance in the multicomponent synthesis of pyridoimidazoisoquinolines

Abstract: A sonochemical approach for the one-pot three-component synthesis of pyridoimidazoisoquinolines via by using phthalaldehyde, trimethylsilylcyanide and aminopyridines the presence of a catalytic amount of a new nanomagnetic catalyst FeO@SiO-CO-CH-NH is described. The characterization of the nanocatalyst and the product was done by various methods, such as FT-IR, SEM, EDX, TGA/DTA, NMR, MS and CHN analyses. This is the first design, preparation, characterization and application of the present core/shell nanomate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
14
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

4
5

Authors

Journals

citations
Cited by 44 publications
(14 citation statements)
references
References 25 publications
0
14
0
Order By: Relevance
“…Concisely, ultrasonication leads to obtain high reaction yield during a short reaction time, under a milder condition. Moreover, physical properties like well dispersion is effectively enhanced by ultrasonication 21–25 . In this study, we intend to introduce a convenient synthetic strategy for a novel medicinal conjugation including CPP hexapeptide and LVX, which passes through a comparative viewpoint between two different heterogeneous magnetic catalytic systems.…”
Section: Introductionmentioning
confidence: 99%
“…Concisely, ultrasonication leads to obtain high reaction yield during a short reaction time, under a milder condition. Moreover, physical properties like well dispersion is effectively enhanced by ultrasonication 21–25 . In this study, we intend to introduce a convenient synthetic strategy for a novel medicinal conjugation including CPP hexapeptide and LVX, which passes through a comparative viewpoint between two different heterogeneous magnetic catalytic systems.…”
Section: Introductionmentioning
confidence: 99%
“…Then, an intermediate was formed from 1 ‐ naphthylamine and 1,4 ‐ dihydroquinoline during ring formation by removing an H 2 O molecule. In the final step, MCSA‐promoted the oxidation of 1,4 ‐ dihydroindenoquinolines to the target product indenoquinolines (Scheme ).…”
Section: Resultsmentioning
confidence: 99%
“…Maleki et al reported Fe 3 O 4 @SiO 2 -CO-C 6 H 4 -NH 2 as a new catalyst for the ultrasonic wave-mediated, rapid synthesis of pyridoimidazoisoquinolines (221) from o-phthalaldehyde (21g), trimethyl silane cyanide (169b) and 2-amino pyridines (150a) in ethanol in excellent yields (Scheme 118). 242 The Fe 3 O 4 @SiO 2 NPs were prepared and functionalized with 4-amino benzoyl chloride, which characterized via SEM, EDX, TGA and DTA. The heterogeneous catalyst was recycled consecutively for up to ve runs without decay in its catalytic activity.…”
Section: Fenp-catalyzed Synthesis Of Heterocyclesmentioning
confidence: 99%